Microscopic cuticle structure comparison of pupal melanic and wild strain of Spodoptera exigua and their gene expression profiles in three time points. (January 2018) - Jan, Saad; Li, Chunyu; Liu, Sisi; Liu, Xiangyang; Zhu, Fuxing; Hafeez, Muhammad; Wang, Mo
Abstract: The beet armyworm, Spodoptera exigua (Hubner), is one of the major crop pests and is a target for current pest control approaches using insecticides. S. exigua melanic mutants (SEM) spontaneously occurred in the S. exigua wild type (SEW) strain and have been maintained under laboratory conditions on an artificial diet. Scanning electron microscopy showed that the inner cuticle of the SEM had a denser and less orderly structure. We investigated the cuticle protein genes using RNA-seq at three different developmental stages of both SEM and SEW. Comparison of cDNA libraries showed that 7257 CPs were significantly up-regulated and 664 genes were significantly downregulated in SEM at the developmental stage of 46-h in the fifth instar. In addition, 460 genes were significantly up-regulated and 439 genes were significantly down-regulated in the SEM at the development stage of 4-h before pupation. Moreover, 162 genes were significantly up-regulated and 293 genes were significantly downregulated in the SEM, just after pupation. Two genes CPR63 and CPR97 were identified from RNA sequences to verify the differentially expressed gene (DEG) results through quantitative real-time PCR (qRT-PCR). The results show that expression of both CPR63 and CPR97 structural cuticular proteins were significantly different between SEM and SEW. This functional analysis may help in understanding the role that these genes play in the cuticle pattern of the SEM. Highlights: Pupal melanic individuals spontaneously occurred in the wild-type Spodopteraexigua population under laboratory conditions. Scanning electron microscopy showed that the inner cuticle of the SEM had a denser and less orderly structure. Analyze the expression of CPs gene in the epidermis of two strains of Spodoptera exigua . The expression of RR-2 subfamily genes increased in SEM compared with SEW. Also the gene expression profiles could give guidance on evolutionary change and genetic changes in Spodopteraexigua .